The Eyjabakkajokull glacial landsystem, Iceland: Geomorphic impact of multiple surges - Schomacker, Anders; Benediktsson, Ivar Örn; Ingolfsson, Olafur (Geomorphology, 2014)
A new glacial geomorphological map of the Eyjabakkajokull forefield in Iceland is presented. The map covers c. 60 km(2) and is based on high-resolution aerial photographs recorded in August 2008 as well as field checking. Landforms are manually registered in a geographical information system (ArcGIS) based on inspection of orthorectified imagery and digital elevation models of the area. We mapped subglacially streamlined landforms such as flutes and drumlins on the till plain, supraglacial landforms such as ice-cored moraine, pitted outwash, and concertina eskers, and ice-marginal landforms such as the large, multi-crested 1890 surge end moraine and smaller single-crested end moraines. The glaciofluvial landforms are represented by outwash plains, minor outwash fans, and sinuous eskers. Extramarginal sediments were also registered and consist mainly of old sediments in wetlands or locally weathered bedrock. Eyjabakkajokull has behaved as a surge-type glacier for 2200 years; hence, the mapped landforms originate from multiple surges. Landforms such as large glaciotectonic end moraines, hummocky moraine, long flutes, crevasse-fill ridges, and concertina eskers are characteristic for surge-type glaciers. The surging glacier landsystem of Eyjabakkajokull serves as a modern analog to the landsystems of terrestrial paleo-ice streams. (C) 2013 Elsevier B.V. All rights reserved.